1998
DOI: 10.1007/s11745-998-0224-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary marine oils and olive oil on fatty acid composition, platelet membrane fluidity, platelet responses, and serum lipids in healthy humans

Abstract: The influence of various dietary marine oils and olive oil on fatty acid composition of serum and platelets and effects on platelets and serum lipids were investigated as part of an extensive study of the effects of these oils on parameters associated with cardiovascular/thrombotic diseases. Healthy volunteers (266) consumed 15 mL/d of cod liver oil (CLO); whale blubber oil (refined or unrefined); mixtures of seal blubber oil and CLO; or olive oil/CLO for 12 wk. In the CLO, seal oil/CLO, and whale oil groups, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0
5

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 42 publications
5
46
0
5
Order By: Relevance
“…Previous intervention studies have shown that distinctive components of MD reduce platelet function, and this effect has been proposed as a mechanism contributing to the CV benefit of this diet. In fact, fish oils (Goodnight et al, 1981;Agren et al, 1997;Vognild et al, 1998), a-linolenic acid (Renaud & Nordøy, 1983;Allman et al, 1995;Freese et al, 1994) and various spices (Janssen et al, 1998;Ackerman et al, 2001;Srivastava et al, 1995) induce a decrease of platelet function. The apparent discrepancy of our results with those findings is probably explained by the lower content of each one of these substances in the complete MD, as opposed to the amounts used for single components of MD in selective intervention studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous intervention studies have shown that distinctive components of MD reduce platelet function, and this effect has been proposed as a mechanism contributing to the CV benefit of this diet. In fact, fish oils (Goodnight et al, 1981;Agren et al, 1997;Vognild et al, 1998), a-linolenic acid (Renaud & Nordøy, 1983;Allman et al, 1995;Freese et al, 1994) and various spices (Janssen et al, 1998;Ackerman et al, 2001;Srivastava et al, 1995) induce a decrease of platelet function. The apparent discrepancy of our results with those findings is probably explained by the lower content of each one of these substances in the complete MD, as opposed to the amounts used for single components of MD in selective intervention studies.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, some of the beneficial effects of MD and wine consumption could be mediated by a reduction in platelet reactivity. Several studies report that diets enriched with fish, a-linolenic acid and spices, abundant in the case of MD, include substances that reduce or could reduce platelet function (Vognild et al, 1998;Allman et al, 1995;Janssen et al, 1998;Ackerman et al, 2001;Srivastava et al, 1995). Similarly, other reports indicate that the intake of moderate amounts of ethanol or nonalcoholic components of wine, for 2 or more weeks, is associated with a decrease in ex vivo platelet function (Pikkar et al, 1987;Pellegrini et al, 1996;Pace-Asciak et al, 1996;Freedman et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Dietary intervention studies show that EPA and DHA in fish=fish oil can be effectively incorporated into platelets in humans (Vidgren et al, 1997;Nelson et al, 1997;Vognild et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The iodine index was significantly correlated with the (Vognild et al, 1998). The seed oil of orange had considerable amounts of oleic fatty acid, with oil-seeds Pera-rio highest value obtained, 29.31%.…”
Section: Resultsmentioning
confidence: 90%